Extension Model of Administration and Management for Business of Community Enterprise - Pensiri Paijit; Chalermsak Toomhirun; Jinda Khlibtong; Tippawan Limunggura (Asia Social Issues, 2023)
This research was aimed to 1) Study successful implementation of community enterprises, 2) Study factors relating to administration and management for business of community enterprises, 3) Analyze, synthesize, and develop the extension model of administration and management for business of community enterprises, and 4) Assess the extension model of administration and management for business of community enterprises. The research method was Mixed Method. The tools used were an In-Depth Interview with purposive sampling of 8 Key informants and a Survey of 520 cases with a Structured Interview. Descriptive Statistics, Comparative statistics (T-test), Factor Analysis, and Multiple Regression Analysis were used. The results found that the factors related to business administration and management, product distribution plans, and marketing were at a high level ( = 4.19, SD.= 0.908), raw material quality inspection or source selection was at the highest level ( = 4.25, SD.= 0.892), continuous communication with community enterprise customers was at a high level ( = 4.03, SD.= 0.966). All 3 components, which were Business Operation, Business administration, and Business Promotion and Support components, affected the success of business administration and management. They could explain 41.10% of the variation in management success and business management services.
Keywords: Financial Reporting and Valuation Research